Effort‐reward imbalance and ambulatory blood pressure among female Las Vegas hotel room cleaners. Issue 6 (1st May 2019) - Feaster, Matthew; Arah, Onyebuchi A.; Krause, Niklas
Abstract: Background: Effort‐reward imbalance (ERI) was hypothesized to be associated with ambulatory blood pressure (ABP) and pulse pressure (PP) among female hotel room cleaners. Methods: ERI, ABP, and PP were assessed among 419 cleaners from five hotels during 18 waking hours. Adjusted linear regression models were used to assess associations of ERI with ABP and PP during 18‐hours, work hours, and after work hours. Results: There was a pattern of higher ERI being associated with higher 18‐hour systolic ABP and 18‐hour PP although the results were imprecise. An increase of ERI by half its range was associated with a 1.6 mmHg (95% CI, −1.6‐4.7) increase in 18‐hour systolic blood pressure (SBP) and a 0.7 mmHg (95% CI, −1.1‐2.5) increase in 18‐hour PP. An increase in rewards by half its range was associated with a 2 mmHg decrease in after‐hours SBP (−2.2, 95% CI, −5.4‐1.0) and after‐hours PP (−1.9, 95% CI, −3.8‐0.0). Among females 45 years or older, ERI was associated with 2.1 and 2.2 mmHg increase in 18‐hour and work hours diastolic ABP, respectively, compared to a 0 mmHg change in 18‐hour and work hours diastolic ABP in younger women. The number of dependents at home attenuated the association. Conclusions: ERI was positively associated with ABP, particularly SBP, and the association was modified by age and the number dependents at home, although the estimates were imprecise. Workplace interventions that integrate stress management and active ABP surveillance appear warranted. However, larger studies with Latina women need to confirm our results.